A new record of the genus Discoelius Latreille, 1809 (Hymenoptera: Vespidae: Eumeninae) from Northern Vietnam with description of two new species - Nguyen, Lien Thi Phuong (Zootaxa, 2016)
The genus Discoelius Latreille, 1809, is newly recorded from Vietnam. Discoelius aurantiacus Nguyen, sp. nov. and D. nigerrimus Nguyen, sp. nov. are described and figured from Northern Vietnam (Lao Cai).